2017
DOI: 10.1002/1873-3468.12761
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the defensin NsD7 in complex with PIP2 reveals that defensin : lipid oligomer topologies are dependent on lipid type

Abstract: Defensins are innate immune molecules that upon recognition of specific phospholipids can disrupt microbial membranes by forming oligomeric assemblies. Structures of two related plant defensins, NaD1 and NsD7, bound to phosphatidylinositol 4,5-bisphosphate (PIP ) and phosphatidic acid (PA), respectively, revealed striking differences in their oligomeric topologies. To understand how NsD7 binds different phospholipids and rationalize the different topologies, we determined the structure of an NsD7-PIP complex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 39 publications
6
31
0
Order By: Relevance
“…Different authors have suggested several mechanisms for permeabilization of membranes [9,30]. In recent years some of the oligomeric structures of plant AMPs bound to their membrane target have been reported and their structures were deposited in the Protein Data Bank [20,[31][32][33]. We found that most of the peptides in our dataset were predicted to have at least one amyloidogenic region which strengthens our belief that these regions could help the AMPs to form oligomers.…”
Section: Oligomerization Of Ampssupporting
confidence: 84%
“…Different authors have suggested several mechanisms for permeabilization of membranes [9,30]. In recent years some of the oligomeric structures of plant AMPs bound to their membrane target have been reported and their structures were deposited in the Protein Data Bank [20,[31][32][33]. We found that most of the peptides in our dataset were predicted to have at least one amyloidogenic region which strengthens our belief that these regions could help the AMPs to form oligomers.…”
Section: Oligomerization Of Ampssupporting
confidence: 84%
“…An understanding of the mechanism by which CAPs such as defensins are able to cause membrane permeabilization and cell death is important for their development as antimicrobial and antitumor molecules. The ability of defensins to oligomerize is being increasingly recognized as a critical feature underlying these activities 18 , 19 , 21 , 24 , 30 , 31 . The human defensins HD6 and HBD-1 have both been shown to oligomerize and form nets to trap bacteria 30 , 31 , however, the underlying molecular mechanism of action and any involvement of ligands remain to be clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…The human defensins HD6 and HBD-1 have both been shown to oligomerize and form nets to trap bacteria 30 , 31 , however, the underlying molecular mechanism of action and any involvement of ligands remain to be clearly defined. In plants, the ability of certain defensins to attack and permeabilize target membranes has been shown to be dependent on the recognition of specific membrane phospholipids such as PIP 2 or PA, and subsequent formation of oligomeric defensin–phospholipid complexes 18 , 19 , 21 . Binding of PIP 2 by the plant defensins NaD1 and TPP3 results in defensin oligomerization, membrane permeabilization, and killing of tumor cells as well as fungi 18 , 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NaD1 and TPP3 have been reported to oligomerize in presence of PIP 2 13 , 15 , whereas NsD7 has been reported to oligomerize in presence of PA 16 . Recently, both NaD1 and NsD7 have also been reported to oligomerize in presence of PA and PIP 2 33 . Our findings raise important questions regarding the mechanism of phospholipid-dependent oligomerization of MtDef5.…”
Section: Discussionmentioning
confidence: 99%